Program Aplikasi Steganografi Menggunakan Metode Spread Spectrum pada Perangkat Mobile Berbasis Android - Rojali Rojali; Afan Galih Salman; Teddy Nugraha (Bina Nusantara University, 2012)
The exchange of traffic information in cyberspace grows fast. In all areas of life utilize technology to exchange information. One of the media owned by many people is mobile device such as mobile phone and tablet computer. In fact many people have been using mobile devices for information exchange function, and expect information to be transmitted quickly, accurately, and safely. The information security sent will be very important when the information is confidential. One way to secure information sent is the concealment of information into a media so that information hidden is beyond recognition by the human senses, which is commonly referred to steganography. This research studied and implemented steganography using spread spectrum Method on Android-based mobile devices. The results showed that the inserted image before and after the message was inserted is not different with PSNR value of about 75.